Students’ Thinking Process in Solving Mathematics Problems Oriented to Higher Order Thinking Skills - Djong, Kristoforus Djawa; Lusi, Yutri Kormalina; Lakapu, Meryani; Guterres, Ilda (FKIP Universitas Lampung, 2024)
Abstract: An educator needs to know the thinking process of their students in order to facilitate the transfer of knowledge and skills. HOTS can play a very big role in supporting students' academic achievement, with HOTS students are able to solve problems, and reflect on their problem-solving experience. The purpose of this research is to describe how students' thought process in solving HOTS-oriented mathematics problems. The method used in this research. The subjects in this study consisted of 7 students who were selected using purposive technique. This research starts from the preparation stage, the research implementation stage and the completion stage. The instrument in this research is HOTS-oriented test questions used to determine the thinking process of high, medium and low ability students. The results of this study show that a person's ability or thought process depends on the level of the problem given. Of the seven subjects in working on two different HOTS problems, it was found that there were 2 high ability students who were able to fulfill the indicators of analysis, evaluation and creation. Three other students in question number 1, met all indicators, but in the second question only met the analysis and evaluation indicators. While the other two students in question number 1 met all the indicators, but in the second question did not meet any of the indicators. The results of this study can be used as a reference for lecturers in choosing media, models and learning methods used to transfer knowledge and skills to students. Keywords: thinking process, HOTS, math problems.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp155-165